Population Biology of Barn Owl (Tyto Alba) and its Impact on Rat Control in Tanjung Karang Ricefield - Mohd Na'im (2004)
The population biology of Tyto alba and its impact on rat control were studied in the Tanjung Karang ricefield area. In Sawah Sempadan area, T. alba visited the nest boxes ranged fiom seven to 60 days after the nest boxes were erected. Nest occupation began 43.7 to 58 days after the nest boxes had been visited by T. alba. There were two breeding seasons, firstly fiom November to February and secondly from May to August. Rat damage on plot A (1 box/5ha), B (1 boxlloha), C (1 box/20 ha) and D (1 boxl45ha) for all three paddy growth stages (tillering booting and harvesting) varied according to nest box densities. The average damage levels for plot 4 B, C and D were 0.62%, 0.79%, 1.57% and 2.1 8% respectively. The nest box occupancy in wet and dry season at Sungai Burung area was 72.2%. Nevertheless, nest box occupancy could increase to 83.3% in subsequent wet season. Clutch sizes during the dry and wet season were 5.38 and 4.07 respectively. Percent hatching was 85.7% during the dry season and 79.2% during the wet season. Fledging success for both seasons were greater than 93%. Damage levels to paddy crop during the tillering stage for both seasons were less than 2%. Damage levels during the booting and harvesting stages were also less than 2% but increased to 3.22% and 3.39% respectively during the dry season crop. The home ranges of female T. alba in designated area at Sawah Sempadan were influenced by nest box densities. Female T. alba occupying nest box densities of 1 box per 5 ha, 1 box per 10 ha and 1 box per 20 ha have home range sizes of 5.79 ha, 14.98 ha and 18.84 ha respectively. However, male T. alba ranged over a larger area which might encompass neighbouring nest boxes as evidenced from the home range sizes of 34.14 ha and 39.65 ha in the 1 bod5 ha and 1 bod10 ha densities respectively. Tyto alba fed exclusively on rat (95.15%) with occasionally on shrews (2.73%) and birds (2.12%). The ricefield rat, R&S argentiventer constituted 84.04% of the identifiable rat prey species and the remainder were the wood rat, R. tiomanicus (10.63%) and the house rat, R. r. diardii (5.8%). Pellets collected in January and July in Sawah Sernpadan Area respectively showed 61.1% and 69.2% of the rat prey were juveniles. Whereas, pellets collected in December and May showed a higher percentage of headless prey i.e. 76.2% and 68.4% respectively. Feeding trial in the Aviary showed that Tyto alba could consume up to three adult rats per night, with an average prey consumption of 174 g preylday, where the owl preferred medium size rats (50-80g) but when taking larger rats (>150g) it only consumed the head.